Improving the Understanding and implementation of MSME Financial Statement Accourding to SAK EMKM - Eskasari Putri; Ashar Mukhammad Akbar; Aini Nur Laila; Ilham Nuryana Fatchan; Fatchan, Fuad Hudaya (Universitas Muhammadiyah Surakarta, 2025)
This community service aims to improve the understanding and ability of business actors in preparing financial statements. Based on the results of initial observations, the majority of actors do not have systematic financial records and do not know the applicable financial reporting standards. This problem has an impact on low business accountability and difficulties inaccessing financing from financial institutions. The method of implementing activities includes socialization, training, and assistance in the preparation of simple financial statements. This activity was carried out offline for three weeks by involving business actors from the goods and services business sector. The results of the activity showed an increase in participants’understanding of the importance of financial statements as well as their ability to prepare simple income and balance sheets. In addition, participants began to implement regular daily transaction logging. This program is expected to help business actors in increasing financial transparency and competitiveness of their businesses in the future.